Sows Fecundity by the Maintenance System - Diana Marin; Cornelia Petroman; Ioan Petroman; Ramona Ciolac; Iasmina Iosim; Ana Lozici; Ioana Pandur (Scientific Papers Animal Science and Biotechnologies, 2023)
Fecundity registered by the females housed in group boxes, with different capacities, has an average of 85.11 ± 1.48, the best results obtained for females housed in boxes with a capacity of 7 heads, 87.39 ± 1, 47. The proportion of pregnant female at 28 days after artificial insemination decreases with increasing number of animals housed in boxes, so in the case of the animals kept in boxes of 14 animals, fecundity at 28 days was 84.17 ± 0, 93, and in the case of animals kept in boxes with capacity of 28 animals, the fecundity at 28 days was 83.76 ± 2.05. The difference between fecundity recorded in case of animals maintained in boxes of 7 heads was significant compared to fecundity of animals maintained in boxes with 14 and 28 heads (χ2 test p <0.001).